2010
DOI: 10.4103/0019-5545.58895
|View full text |Cite
|
Sign up to set email alerts
|

Profile of risk factors associated with suicide attempts: A study from Orissa, India

Abstract: Context:Periodic systematic profiling of suicidal risk factors in developing countries is an established need.Aims:It was intended to study the risk factors associated with suicide attempts in Orissa, one of the most economically compromised states of India.Settings and Design:Cross-sectional study in a general hospital.Materials and Methods:Consecutive 149 suicide attempters were evaluated for psychosocial, situational, and clinical risk factors using the Risk Rescue Rating scale, Suicide Prevention Center sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

23
72
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(98 citation statements)
references
References 32 publications
(45 reference statements)
23
72
3
Order By: Relevance
“…[1018] The gap between male and female suicide rates in India is relatively small. [19] There are reports of both male and female predominance in suicide attempts in hospital-based studies in India.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1018] The gap between male and female suicide rates in India is relatively small. [19] There are reports of both male and female predominance in suicide attempts in hospital-based studies in India.…”
Section: Discussionmentioning
confidence: 99%
“…[10] The male-to-female ratio was closer to one in adults and around 1:3 in adolescents in a recent study. [18] In comparison to seven other world communities in the WHO SUPRE-MISS study that showed female preponderance, Chennai was the only site which showed a greater number of males (68%). [21]…”
Section: Discussionmentioning
confidence: 99%
“…The results of a Belgium study [28] on life events of suicide attempters showed that 8 (42.1%) of them had relational problems, but the majority of them had academic failures since majority of the study subjects were adolescence. Another international study [29] also supported the present study results that 44 (72.1%) of the study subjects had family-related conflicts and 39 (63.9%) of them had marital conflicts.…”
Section: Discussionmentioning
confidence: 99%
“…Understanding these stressors largely contribute to the future prevention strategies. Studies assessing stress full life events and suicidal intent are done nationally and internationally [16][17][18][19]. These studies mainly try to focus on one aspect of the stressors.…”
Section: Introductionmentioning
confidence: 99%
“…A study on burns victims found that being in a joint family was a risk factor for dowry deaths [26]. Another study found that family and marital conflict was a major reason for intentional deaths [27]. It has been reported that rigidly defined roles and interpersonal stressors, which are found more frequently in a joint family, may lead to more psychiatric problems [10].…”
Section: Discussionmentioning
confidence: 99%